Relationship between occupational and leisure-time physical activity and the need for recovery after work - Tiina Karihtala; Anu M. Valtonen; Hannu Kautiainen; Leila Hopsu; Janne Halonen; Ari Heinonen; Sampsa Puttonen (BMC, 2023)
Abstract Background Health benefits of physical activity are very well acknowledged but the role of both occupational physical activity (OPA) and leisure time physical activity (LTPA) in recovery after work is not thoroughly understood. The purpose of this study was to investigate the association between accelerometer-measured OPA and LTPA and the need for recovery after work (NFR) in early childhood education and care (ECEC) professionals. Methods The study participants were 217 female ECEC professionals aged 17-64. Physical activity was recorded with a three-axis accelerometer (ActiGraph GT9X Link, ActiGraph, USA) for seven consecutive days. Separate analyses were conducted for both OPA and LTPA and reported as hours/day based on different intensity levels (light, moderate, vigorous, very vigorous). The NFR was measured with the Need For Recovery (NFR) scale (0%-100%). Results Participants' average physical activity for both OPA and LTPA was about 4 h/day, and the mean NFR score was 38.4%. OPA was significantly associated with the NFR but not with LTPA. The relationship remained significant after adjustments for age, body mass index, work ability, mental health status, and sleep difficulties (p < 0.024). Conclusion According to this study, the OPA level is related to the level of the NFR in female ECEC professionals. Based on the results, it seems that LTPA has no relevance to the NFR. Results suggest that long-lasting OPA, even without strenuous physical activity at work, may predispose individuals to a high NFR.